2013
DOI: 10.1371/journal.pone.0071603
|View full text |Cite
|
Sign up to set email alerts
|

The TRPA1 Agonist, Methyl Syringate Suppresses Food Intake and Gastric Emptying

Abstract: Transient receptor potential channel ankryn 1 (TRPA1) expressed in the gastrointestinal tract is associated with gastric motility, gastric emptying, and food intake. In this study, we investigated the effects of methyl syringate, a specific and selective TRPA1 agonist, on food intake, gastric emptying, and gut hormone levels in imprinting control region (ICR) mice. The administration of methyl syringate suppressed cumulative food intake and gastric emptying. In addition, treatment with ruthenium red (RR), a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 40 publications
2
45
2
Order By: Relevance
“…In addition, bitterness is known as a taste signal that anticipates non-nutritional components or toxins in foods (26). These findings (22)(23)(24)(25)(26), together with our present results raise the possibility that the transient fullness perception after oral carbonation may be explained by the activation of TRPA1 and TRPM8 induced by the taste of carbonated water and the physical stimulus of feeling coldness.…”
Section: Appetite Feelingssupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, bitterness is known as a taste signal that anticipates non-nutritional components or toxins in foods (26). These findings (22)(23)(24)(25)(26), together with our present results raise the possibility that the transient fullness perception after oral carbonation may be explained by the activation of TRPA1 and TRPM8 induced by the taste of carbonated water and the physical stimulus of feeling coldness.…”
Section: Appetite Feelingssupporting
confidence: 71%
“…It has been reported that carbon dioxide activates transient receptor potential channel ankyrin 1 (TRPA1) and also that it is perceived as a tingling sensation in the oral cavity (3). Some animal experiments revealed that TRPA1 agonists, such as methyl syringate, altered gastrointestinal functions (22,23) and suppressed the amount of food intake (22), suggesting that TRPA1 is responsible for appetite regulation. Moreover, the perception of coldness (15˚C) may be related to the activation of transient receptor potential melastatin 8 (TRPM8) (24).…”
Section: Appetite Feelingsmentioning
confidence: 99%
“…Moreover, AITC administration by gavage or administration into the duodenum increased plasma GLP-1 concentration (43); however, the effect was preserved in TRPA1 knockout mice suggesting existence of other pathways for increasing GLP-1 secretion. In contrast, a recent study did not find difference in GLP-1 levels following activation of TRPA1 with methyl syringate, while increased peptide YY levels, decreased food intake and gastric emptying was observed (81). Taken together, a variety of findings suggest that TRPV1 and TRPA1 may have potential for modulating ghrelin and/or GLP-1 secretion.…”
Section: Trpv1 Trpa1 and Secretion Of Ghrelin And Glucagon-like Peptmentioning
confidence: 80%
“…Reports of other active ingredients, with the exception of cinnamaldehyde, or molecular pathways responsible for the above‐mentioned effects are relatively unknown and inconsistent. Anti‐obesity and antidiabetic properties of cinnamon are often attributed to its major flavoring component, cinnamaldehyde, which has been shown to reduce short‐term energy intake and cumulative body weight in animal models . Besides a delay in gastric emptying rates, which has been associated with reduced hunger and increased satiety, regulation of satiety‐ and appetite‐related hormones might play a role in the cinnamaldehyde‐induced effect on energy intake .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reduced fasting‐induced hyperphagia and upregulated mRNA expression of hypothalamic neuropeptides associated with satiety after chronic cinnamaldehyde supplementation (10 mg kg −1 body weight) in mice, cinnamaldehyde was also found to modulate the secretion of satiety‐related gut hormones, including peptide YY (PYY) or serotonin …”
Section: Introductionmentioning
confidence: 99%